Critical success factors for the implementation and adoption of e-learning for junior health care workers in Dadaab refugee camp Kenya - Aude D. Burkardt; Nicerine Krause; Minerva C. Rivas Velarde (BMC, 2019)
Abstract This paper presents the results of a case study that analyses the critical factors that influence the implementation of professional health education via blended learning in Dadaab refugee camp. It explores innovative solutions to the issues facing refugees looking for professional health training, namely the health workforce shortage and lack of training opportunities. It outlines social and political factors that impact professional health education for refugee youth. It outlines barriers and facilitators on the implementation of 'Distance Basic Training of Healthcare Professionals', a blended training course provided by the University of Geneva to junior health care personnel in Dadaab Refugee camp. Methods This case uses mixed methods. Descriptive statistics drawn from online surveys, learning analytics data, and exchanges on online forums and student chat groups are all used. Qualitative methods consist of two focus groups, comprising of all students (n = 27) were convened, as well as, individual semi-structured interviews with 14 of the 27 students; three with managers from the health service who supervised enrolled students; and two with senior managers who were responsible for staff and training decision-making. Qualitative data was transcribed, and thematic analyses were applied. Results The results demonstrate that barriers for the implementation of professional education in a refugee camp emerged not only from the constraints on the environment, but also from barriers stemming from legislation and administrative procedures. Data suggested weaknesses on the education system could be addressed by providing students with extra-curricular support, information and communications technology (ICT) literacy, and promoting mechanisms for peer support while broadening entry requirements to increase the enrolment of female students. Finally, providing internationally credentialed courses and transferable skills enables professional pathways for refugee students. Discussion Blended learning enables the design and delivery of high-quality medical education that is sustainable and relevant in a particular environment, e.g. refugee camps. Furthermore, the research reveals that building education pathways could enhance numbers of health workers with the appropriate skillset to serve communities.